2015
DOI: 10.1016/j.mehy.2014.12.014
|View full text |Cite
|
Sign up to set email alerts
|

The use of shear rate–diameter dose–response curves as an alternative to the flow-mediated dilation test

Abstract: Lee (2015) The use of shear rate-diameter dose-response curves as an alternative to the flow-mediated dilation test. Medical Hypotheses, 84 (2). pp. 85-90. ISSN 0306-9877 Official URL: http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…According to Stoner et al, there are a few main limitations associated with the standard FMD methodology: first, inappropriate expression of FMD, second, measurement variance associated with a short-lived FMD response, third, most studies fail to account for the FMD stimulus, and lastly, poor reproducibility [ 122 , 123 ].…”
Section: Current Limitations Of Fmd Procedures and Future Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Stoner et al, there are a few main limitations associated with the standard FMD methodology: first, inappropriate expression of FMD, second, measurement variance associated with a short-lived FMD response, third, most studies fail to account for the FMD stimulus, and lastly, poor reproducibility [ 122 , 123 ].…”
Section: Current Limitations Of Fmd Procedures and Future Trendsmentioning
confidence: 99%
“…It has been shown that shear rate-diameter dose–response curves could improve the traditional FMD measurement and serve as a superior clinical and research tool for assessing cardiovascular disease risk in various populations [ 123 ].…”
Section: Current Limitations Of Fmd Procedures and Future Trendsmentioning
confidence: 99%
“…Modeling of the shear-dilatory, dose-response ( 23) or exposure-response (24) relationship has been previously suggested as an alternative means to evaluate FMD; however, these prior models would require clinically prohibitive changes in how FMD is measured (23) and face parameter identifiability issues (24). In the present study, we developed an exposure-response modeling approach to derive parameters from the FMD test that describe both the shear exposure and diameter response.…”
mentioning
confidence: 99%